PERAN PENGAWAS DALAM PENINGKATAN KOMPETENSI PEDAGOGIK GURU PENDIDIKAN AGAMA ISLAM SMP NEGERI 10 - Harmida Ramadhani Nasution, Rahmadi Ali (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
The research problem was how the planning, implementation, problems and solving the problems which supervisor did in improving Islamic teachers’ pedagogic competencies at Government Junior School 10 Binjai, Binjai City, North Sumatera. The purpose of the study was to describe the planning, implementation, problems and solving the problems which supervisor did in improving Islamic teachers’ pedagogic competencies at Government Junior School 10 Binjai, Binjai City, North Sumatera. This research was conducted with qualitative methods. Research data collection was done by using interview, observation and documentation studies. Data analysis was done by using data reduction, data display, and conclusion, that the process took place in a circular during the study.The supervisor’s planning in improving Islamic teachers’ pedagogic competencies at State Junior High School 10 Binjai, Binjai City, North Sumatera conducted in early academic year and involving supervisors, principal, and the teachers. Planning arranged systematically in the Work Plan Trustees.The implementation of improving Islamic teachers’ pedagogic competencies at State Junior High School 10 Binjai, Binjai City, North Sumatera done in two ways: personal approach and group approach. Personal approach consisted of direct class visits, personal meeting and class observation. Group approach consisted of periodical meeting, the empowerment of Islamic Teachers Organization and trainings.Problems faced by Supervisor in improving Islamic teachers’ pedagogic competencies at State Junior High School 10 Binjai, Binjai City, North Sumatera were: 1) Technical problems, consisted of urgent unplanned worktrip and the large workfield which reduced meeting intensity with Islamic teachers; and 2) Non technical problems, which consisted of changing of national curriculum and changing of Teaching Plan Form. These several changes caused misunderstood among Islamic teachers.Supervisor solved the problems faced in improving Islamic teachers’ pedagogic competencies at State Junior High School 10 Binjai, Binjai City, North Sumatera by building effective communication with teachers, improving his personal performance and empowering Islamic Teachers Organization monthly.